The impact of socialisation services in the whole process of agricultural production on food security—quasi-natural experimental evidence from China - Tao, Ying; Zhao, Cuiping (Frontiers in Sustainable Food Systems, 2024)
Abstracts:Food security (FS) is an important guarantee for world peace and development and the basis for building a community of human destiny, which has a bearing on the sustainable development and future destiny of humankind.This study empirically analysis the relationship between socialisation services in the whole process of agricultural production (ASS) and guaranteeing FS, as well as the path of their role, using provincial panel data from 2010-2022 in China as an example, using the double-difference method.The regression results show that ASS can have the ability to contribute to the level of FS, and the conclusion still holds after a series of robustness tests.The results of the heterogeneity analysis show that the role of ASS in guaranteeing FS receives the influence of the level of agricultural development in each region, while it plays a greater role in the main food-producing areas.The mechanism analysis analyses the mechanism of the role of ASS in the whole process of agricultural production in guaranteeing FS from the three links of pre-production, mid-production and post-production respectively, and finds that ASS in the whole process of agricultural production is able to guarantee FS by reducing the cost of purchasing means of production in the pre-production stage, fostering a new type of agricultural management main body in the mid-production stage, and increasing the income of farmers' household management in the post-production stage.Based on the above findings, this study proposes corresponding policy recommendations.This study can provide insights for ensuring world FS and contribute to maintaining social stability and development. The conclusions of the study are universally applicable, and all countries in the world can benefit from and draw lessons from it.